Optimization and Characterization of Physical–Mechanical Properties of Biodegradable Edible Films Based on Pectin from Breadfruit Peel for Food Packaging - Mappamadeng, Andi Hidayatullah; Amalia, Rizka (Journal of Vocational Studies on Applied Research, 2022)
This study aims to determine the characteristics and optimization of biodegradable films based on pectin from breadfruit peel. The study was employed using a factorial design with multiple variables: pectin (2 and 4 grams), sorbitol concentration (10% and 20%) and drying temperature (1200C and 1400C) were studied. The results obtained from eight samples showed that the water vapor transmission rate was in the range of 3.525 - 6.952 g/m2.day. The best-achieved water vapor transmission rate (3,525 g/m2.day) was obtained at specific operating conditions, namely 4 grams of pectin, 20% of sorbitol concentration and drying temperature of 1400C. In this study, the most influential factor for water vapor transmission rate is pectin weight with the value effect of -1.238. The highest tensile strength test and percentage elongation were 116.55 kgf/cm2 and 10%, respectively. The FTIR analysis showed that the pectin from breadfruit peel was according to commercial pectin standard, by the presence of OH and ester (COOH) groups. The SEM Analysis showed  that the molecular structure of edible films did not look porous, dense, but not flat on its surface, thus less permeable to air.